Analysis of Physical And Non-Physical Work Environment PT. Kakiatna Indonesi To Company Performance - Prasastia, Nucki; Zuhriah, Syarifah (Journal of Economics and Business UBS, 2019)
Company performance in organizations is influenced by many factors among the most important is the influence of physical and non-physical work environment. This research was carried out with the aim of knowing the extent to which the physical and non physical work environment elements affect the company's performance, the research method uses a quantitative descriptive approach involving 30 respondents from 85 populations.     Based on the results of multiple linear regression analysis shows that there are positive and significant effects of physical and non-physical work environment on company performance. The coefficient of determination shows that the performance of PT. Kakiatna Indonesia is influenced by physical and non-physical work environment by 59.0% while the remaining 41.0%.             Based on the research concluded that partially the physical work environment variable correlates to the company's performance, partially the non-physical work environment variable correlates with the company's performance and it is concluded that the physical and non-physical work environment together / simultaneously correlates with the company's performance.